2022
DOI: 10.3389/fpls.2022.988627
|View full text |Cite
|
Sign up to set email alerts
|

Soil and foliar selenium application: Impact on accumulation, speciation, and bioaccessibility of selenium in wheat (Triticum aestivum L.)

Abstract: A comprehensive study in selenium (Se) biofortification of staple food is vital for the prevention of Se-deficiency-related diseases in human beings. Thus, the roles of exogenous Se species, application methods and rates, and wheat growth stages were investigated on Se accumulation in different parts of wheat plant, and on Se speciation and bioaccessibility in whole wheat and white all-purpose flours. Soil Se application at 2 mg kg–1 increased grains yield by 6% compared to control (no Se), while no significan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
12
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 60 publications
1
12
0
Order By: Relevance
“…The fact that the translocation of inorganic Se to the reproductive organs is minimal is advantageous to produce fortified food products since inorganic Se is more toxic than its organic counterparts (Rayman et al, 2008 ). These findings agree with previous studies on wheat, even though our conditions led to lower amounts of inorganic Se and a higher percentage of SeCyst (Di et al, 2023 ; Wang et al, 2022 ; Wang, Ali, et al, 2020 ).…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…The fact that the translocation of inorganic Se to the reproductive organs is minimal is advantageous to produce fortified food products since inorganic Se is more toxic than its organic counterparts (Rayman et al, 2008 ). These findings agree with previous studies on wheat, even though our conditions led to lower amounts of inorganic Se and a higher percentage of SeCyst (Di et al, 2023 ; Wang et al, 2022 ; Wang, Ali, et al, 2020 ).…”
Section: Discussionsupporting
confidence: 93%
“…Selenate is also commonly quantified, with literature reporting values below 5% (Galinha et al, 2015;Warburton & Goenaga-Infante, 2007). An extremely limited number of studies have achieved a successful determination of the five Se species (Di et al, 2023;Eiche et al, 2015;Hart et al, 2011;Wang et al, 2022;Wang, Ali, et al, 2020;Xiao et al, 2021), and the present study is the first to quantify six species in wheat. Likewise, very few have used complementary techniques to confirm species identification and validate the applied method (Aureli et al, 2012;Warburton & Goenaga-Infante, 2007).…”
mentioning
confidence: 86%
“…This study is consistent with the findings of previous studies, which emphasize that SeMet is generally the principal organic species found in Se-enriched staple crops. For example, wheat can store 87–96% of SeMet and 4–13% SeCys 2 in the grains as an edible part, regardless of the application rate of exogenous Se . Similarly, SeMet was extracted in wheat (∼90%) and about 65–87% of total extractable Se species in Se-enriched wheat flour and bread .…”
Section: Discussionmentioning
confidence: 99%
“…The main form of fertilized-derived Se in grains was SeMet with an abundance of ∼92% in Zea mays L., ∼63% in cowpea, and ∼85.2% in groundnuts . Wang et al revealed in a recent study that SeMet (∼96%) and SeCys 2 (∼8%) were the main Se forms identified in grains of wheat, and inorganic Se accumulation of Se­(VI) was found in wheat leaves. The predominant organic form in garlic is SeMeCys (with anticarcinogenic properties), and similarly onion contained SeMeCys as a major forms, while major organic and inorganic forms in broccoli were SeMeCys, Se­(IV) and Se­(VI) …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation